Dietary methionine restriction alleviates oxidative stress and inflammatory responses in lipopolysaccharide-challenged broilers at early age - Pang, Xiyuan; Miao, Zhiqiang; Dong, Yuanyang; Cheng, Huiyu; Xin, Xiangqi; Wu, Yuan; Han, Miaomiao; Su, Yuan; Yuan, Jianmin; Shao, Yuxin; Yan, Lei; Li, Jianhui (Frontiers in Pharmacology, 2023)
In this study, we investigated the effect of dietary methionine restriction (MR) on the antioxidant function and inflammatory responses in lipopolysaccharide (LPS)-challenged broilers reared at high stocking density. A total of 504 one-day-old male Arbor Acre broiler chickens were randomly divided into four treatments: 1) CON group, broilers fed a basal diet; 2) LPS group, LPS-challenged broilers fed a basal diet; 3) MR1 group, LPS-challenged broilers fed a methionine-restricted diet (0.3% methionine); and 4) MR2 group, LPS-challenged broilers fed a methionine-restricted diet (0.4% methionine). LPS-challenged broilers were intraperitoneally injected with 1 mg/kg body weight (BW) of LPS at 17, 19, and 21 days of age, whereas the CON group was injected with sterile saline. The results showed that: LPS significantly increased the liver histopathological score (p < 0.05); LPS significantly decreased the serum total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) activity at 3 h after injection (p < 0.05); the LPS group had a higher content of Interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF)-α, but a lower content of IL-10 than the CON group in serum (p < 0.05). Compared with the LPS group, the MR1 diet increased catalase (CAT), SOD, and T-AOC, and the MR2 diet increased SOD and T-AOC at 3 h after injection in serum (p < 0.05). Only MR2 group displayed a significantly decreased liver histopathological score (p < 0.05) at 3 h, while MR1 and MR2 groups did so at 8 h. Both MR diets significantly decreased serum LPS, CORT, IL-1β, IL-6, and TNF-α contents, but increased IL-10 content (p < 0.05). Moreover, the MR1 group displayed significantly increased expression of nuclear factor erythroid 2-related factor 2 (Nrf2), CAT, and GSH-Px at 3 h; the MR2 group had a higher expression of Kelch-like ECH-associated protein 1 (Keap1), SOD, and GSH-Px at 8 h (p < 0.05). In summary, MR can improve antioxidant capacity, immunological stress, and liver health in LPS-challenged broilers. The MR1 and MR2 groups experienced similar effects on relieving stress; however, MR1 alleviated oxidative stress more rapidly. It is suggested that precise regulation of methionine levels in poultry with stress may improve the immunity of broilers, reduce feed production costs, and increase production efficiency in the poultry industry.